2018
DOI: 10.1155/2018/2979206
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Cardiovascular Disease Risk Estimation Based on Lipid Profile-Based and BMI-Based Framingham Risk Scores across Multiple Sociodemographic Characteristics: The Malaysian Cohort Project

Abstract: Cardiovascular disease (CVD) leads to high morbidity and mortality rate worldwide. Therefore, it is important to determine the risk of CVD across the sociodemographic factors to strategize preventive measures. The current study consisted of 53,122 adults between the ages of 35 and 65 years from The Malaysian Cohort project during recruitment phase from year 2006 to year 2012. Sociodemographic profile and physical activity level were assessed via self-reported questionnaire, whereas relevant CVD-related biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
8
27
0
2
Order By: Relevance
“…This fact was not evidenced in the variables "being illiterate" and "Type 2 DM" being displayed in the final model as non-protective risk factors for cardiovascular health. The risk of developing cardiovascular risk in 10 years was lower among people with higher schooling levels 37 . The findings regarding the educational variable translate important interpretations for monitoring and evaluating hypertensive people's health, considering that knowledge on this variable can elucidate ethnic racial disparities in access to health, since more educated people understand better their health-care process, seek medical and health services more frequently and, therefore, the risk for cardiovascular disease and cardiovascular effects will be lower.…”
Section: Discussionmentioning
confidence: 94%
“…This fact was not evidenced in the variables "being illiterate" and "Type 2 DM" being displayed in the final model as non-protective risk factors for cardiovascular health. The risk of developing cardiovascular risk in 10 years was lower among people with higher schooling levels 37 . The findings regarding the educational variable translate important interpretations for monitoring and evaluating hypertensive people's health, considering that knowledge on this variable can elucidate ethnic racial disparities in access to health, since more educated people understand better their health-care process, seek medical and health services more frequently and, therefore, the risk for cardiovascular disease and cardiovascular effects will be lower.…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that the 10-year risk of CVD in male was 2 to 3 times higher than that in female in all three categories. Previous studies [38,39] indicated that male generally had a higher risk to develop CVD events, which may be related to differences in exposure levels and sensitivities of risk factors for CVD between genders, in addition to sex hormone differences. Both gender showed CLASS3 CVD risk higher than that of both CLASS1 and CLASS2, after the adjustment of confounding factors, found that the risk of CVD in CLASS3 in males was 1.44, 1.34 times compared to CLASS1 and CLASS2.This result is consistent with Petagna's [40] adult health longitudinal study and Li's [9] Meta-analysis consisting of 21 prospective studies involving 20000 patients with CVD de nitely.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing age is known to be associated with cardiovascular risk factors (CVrf ) and therefore cardiovascular events [33]. us, Borhanuddin et al found a higher risk score for male subjects [34]. Female sex was also found to have a lower risk of cardiovascular events [35].…”
Section: Discussionmentioning
confidence: 99%